Microencapsulation of Theobroma cacao L. waste extract: optimization using response surface methodology. (17th February 2017) - Gabbay Alves, Taís Vanessa; Silva da Costa, Russany; Aliakbarian, Bahar; Casazza, Alessandro Alberto; Perego, Patrizia; Carréra Silva Júnior, José Otávio; Ribeiro Costa, Roseane Maria; Converti, Attilio
Abstract: The cocoa extract ( Theobroma cacao L.) has a significant amount of polyphenols (TP) with potent antioxidant activity ( AA ). This study aims to optimise microencapsulation of the extract of cocoa waste using chitosan and maltodextrin. Microencapsulation tests were performed according to a Box–Behnken factorial design, and the results were evaluated by response surface methodology with temperature, maltodextrin concentration ( MD ) and extract flowrate ( EF ) as independent variables, and the fraction of encapsulated TP, TP encapsulation yield, AA, yield of drying and solubility index as responses. The optimum conditions were: inlet temperature of 170 °C, MD of 5% and EF of 2.5 mL/min. HPLC analysis identified epicatechin as the major component of both the extract and microparticles. TP release was faster at pH 3.5 than in water. These results as a whole suggest that microencapsulation was successful and the final product can be used as a nutrient source for aquatic animal feed. Highlights: Microencapsulation is optimised according to a factorial design of the Box–Behnken type. Epicatechin is the major component of both the extract and microcapsules. The release of polyphenols from microcapsules is faster at pH 3.5 than in water.